Penggunaan Internet Sebagai Media Komunikasi Dalam Proses Pelaksanaan Aktivitas Belajar Mahasiswa Di Universitas Dharmawangsa - Junaidi Junaidi; Welnof Satria; Dewi Wahyuni (Mahesa Research Center, 2021)
This study aims to determine the use of the internet and its obstacles as a medium of learning communication in the implementation of learning activities by lecturers to students at Dharmawangsa University. This study uses a qualitative approach, with descriptive methods. The research was conducted at the Dharmawangsa University. The research informants consisted of 6 permanent lecturers and 6 students from 6 faculties. Data collection using interview techniques. The results showed that during the covid 19 period, with online lectures, lecturers and students used learning media provided by Dharmawangsa University in the form of a google classroom with limited facilities that could only convey written materials. To be able to interact directly in the form of oral and video lecturers using Whatsapp media. The obstacles faced by lecturers were problems with the internet network which was sometimes unstable and internet quota, which was also experienced by students. The conclusion of the research on the lecture process using internet media as a medium of learning communication has been able to fulfill online lectures according to the set schedule, it's just that there are still many weaknesses faced in terms of providing internet media facilities so that the lecture process does not run optimally.